Die gesundheitliche Versorgungssituation von Asylsuchenden: Bundesweite Bestandsaufnahme über die Gesundheitsämter = Health care provisions for asylum-seekers : A nationwide survey of public health authorities in Germany - Bozorgmehr, Kayvan; Nöst, Stefan (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
BackgroundNation-wide studies on the health care situation of asylum-seekers in Germany are lacking, but decision-makers increasingly need such information.ObjectivesThe aim of the study was to assess structures, processes and needs related to the health care provision for asylum-seekers along the continuum of reception centres to community dwellings from the perspective of the German public health authorities.Materials and methodsA nation-wide cross-sectional mixed-methods survey was carried out. All heads of public health authorities in Germany (N = 389) were invited to complete a standardized questionnaire related to: (1) medical procedures and screening; (2) prevention and health promotion; (3) communication; (4) documentation and information; (5) coordination; (6) structural resources and needs. The quantitative survey was complemented by qualitative semi-structured interviews.ResultsIn total, 123 heads of public health authorities (response rate: 31,6 %) completed the questionnaire, and 29 were interviewed. Priority areas to improve the health care situation were better coordination and standardisation of care, enhancing vaccination capacities, standardised documentation, better health information exchange (in line with data protection laws), and a stronger focus on a few relevant infectious diseases in the scope of compulsory health entry examinations.ConclusionThe instruments proved useful to assess the health care situation of asylum-seekers in a decentralized health care system. Repeated surveys with a focus on selected domains of the questionnaire could help monitor the health care situation on a regular basis.